Strategies for prevention of adverse events in the administration of medicines by the nursing team (Research, Society and Development, 2023)
The objective of this study was to analyze the scientific evidence related to strategies for preventing adverse events due to medication administration errors by the nursing team published between 2016 and 2020. This is an integrative literature review in the MEDLINE databases, SCIELO, LILACS and BDENF, using the descriptors: Adverse Events, Nursing, Medication Errors. Original articles published during the years 2016 to 2020, in Portuguese, within the proposed theme were included and thesis, dissertation, letter to the reader, review articles, duplicates and articles with more than 4 years of publication were excluded. 14 articles were selected and after analyzing the data, the main interventions found as preventive measures to avoid medication administration errors were: identification bracelet, risk bracelet, electronic prescription, continuing education, bed identification, medication identification, nursing sizing, barcode on medication, checklist, the rule of 9 rights. It was possible to find at least 10 interventions as evidence for the prevention of medication errors. Although interventions do not guarantee 100% safe care, they reduce the risk of exposure to adverse events, thus increasing the quality of nursing care. It was also observed in this study the way in which nursing deals with these medication administration errors, in a punitive way or failing to notify, which in addition to interfering with care, makes it difficult for managers to identify in which phase of the process the errors occur. errors to propose an effective intervention plan.